Degeneration patterns of the worker spermatheca during morphogenesis in ants (Hymenoptera: Formicidae). Issue 2 (March 2016) - Gotoh, Ayako; Billen, Johan; Hashim, Rosli; Ito, Fuminori
Summary: Reproductive division of labor is one of the crucial features in social insects, however, the developmental mechanisms leading to modifications in the reproductive apparatus of workers are still not very clear. Ants show a remarkable diversity in the morphological specialization of the worker's reproductive apparatus, that allows to distinguish four types, type 1: workers that have ovaries and a functional spermatheca, and that reproduce like queens, type 2: workers have ovaries and a vestigial spermatheca, type 3: workers have ovaries but no spermatheca, and type 4: workers lost both ovaries and spermatheca. We investigated morphogenesis of the worker spermatheca in 28 ant species by histological examination. In workers of type 1, the morphogenesis of the spermatheca is very similar to that in ant queens. In type 2, the spermathecal disc also differentiates, however, the development is interrupted and remains vestigial. In types 3 and 4, the absence of the spermatheca in the adult phase is caused by a degeneration after initial formation of the spermathecal disc or by a complete lack of the spermathecal discs. The timing of these interruption and degeneration events varies among species. The species exhibiting an earlier interrupting point of spermatheca formation in workers have a larger queen‐worker dimorphism, that seems to be independent from ant phylogeny.